Effects of intersectoral terms of trade on agricultural output - Hondai, Susumu (Tokyo, Japan : International Development Center of Japan, 1979)
Intersectoral flows of income from agriculture to non-agriculture have been recognized as a necessary process at an early stage of economic development. The terms of trade between non-agriculture and agriculture are one of the variables which affect the inter-sectoral shifts
Bibliography: p. 20.
osc 05/03/2019
Loans
Keywords: Agriculture and state; Agricultural productivity; Input-output analysis; Terms of trade; Japan